Microbial Patterns and Antimicrobial Susceptibility on Pediatric Patients with Pressure Ulcers - Deryne Anggia Paramita; Khairina Nasution; Nova Zairina Lubis (Molecular and Cellular Biomedical Sciences, 2019)
Background: A pressure ulcer (PU) is localized injury to the skin and/or underlying tissue usually over a bony prominence, as a result of pressure, or pressure in combination with sharp surface. Several studies have found that PU is also a common problem in the pediatric population. Infection at PU sites is the most common complication, where PU can host resistant microorganisms and can turn into a local infection that is a source of bacteremia in hospital patients. This study aims to determine the most common bacteria and antimicrobial susceptibility at the site of PU in pediatric patients that serve as baseline data in Haji Adam Malik Hospital.Materials and Methods: A cross-sectional study was carried out in July-December 2017, involving 30 PU pediatric patients. For each subject, swab from ulcers were cultured in microbial laboratory to determine the microbial pattern and antimicrobial susceptibility.Results: The most common age group was 0-3 (53.3%), the highest gender was male (60%), the most common type was type 2 (46.7%), the main location was occipital (30%) and the most common undelying diseases were hydrocephalus (16.6%). The most common microbial pattern in PU pediatric patients is Acinetobacter baumannii (40%). The highest sensitivity is vancomycine for gram positive bacteria and amikacine for gram negative bacteria.Conclusion: The most common microbial pattern in PU pediatric patients in Haji Adam Malik Hospital is Acinetobacter baumannii (40%). The highest sensitivity is vancomycine for gram positive bacteria and amikacine for gram negative bacteria.Keywords: pressure ulcer, pediatric, microbial pattern, antimicrobial susceptibility